Good Governance as Primary Program for the Neo-Liberalism Agenda - Krisnaldo Triguswinri (Social Science Studies, 2021)
This paper aims to enrich the study of good governance as a formula for the government of Indonesia, which in the author's observation, is a proponent that supports and serves the neo-liberalism agenda. In this paper, the author presents the bad reality of good governance which has logical coherence with policy deregulation, privatization, hegemony and capitalization which experiences its internal contradictions with the ideas and motives of democratization as the main proposal of good governance. In addition, literally and figuratively, the author provides a theoretical critique of the logic of neo-liberalism and describes its deception in the public policy process.